Regiochemistry of S-alkyl-substituted alkynes in Pauson-Khand reactions: is a correlation with X-ray data and charge distribution calculations of the Co2(CO)6-alkyne complexes possible? - Schulte, Jan Hilko; Gleiter, Rolf; Rominger, Frank (Organic letters, 2002)
Pauson−Khand reactions (PKR) of RSC⋮CR‘ (6−10) yielded in all cases as the main product the regioisomer with the alkyl-S group disposed α to the CO group (16a−22a). Correlation of these results with X-ray data and charge distribution calculations of the corresponding dicobalthexacarbonyl complexes proves that a recently postulated “trans effect” in these complexes is not suitable for predicting the regiochemical outcome of the PKR unambiguously.